PERAN PSYCHOLOGICAL CAPITAL DAN KOMITMEN ORGANISASI DALAM MEMODERASI PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KOMPETENSI MANAJERIAL PADA KINERJA MANAJERIAL - Parumartha Pande, I Komang Abdi; Dwirandra, A. A. N. B.; Harta Mimba, Ni Putu Sri (Buletin Studi Ekonomi; VOL.22.NO.2. AGUSTUS 2017 (PP 113-261), 2017)
This study aimed to test the performance by integrating the budgetary participation and managerial competence with conditional factors (psychological capital and organization commitment). Performance tested was the managerial performance of Denpasar Water Supply Company. The research was conducted by survey and questionnair distributed to all managers who have a higher management and staff as well as directly involved in the budgeting process. The questionnaire can be used is 36 questionnaires. Data analysis was performed using regression and residual test for equality moderation. The results showed budgetary participation and managerial competence has positive effect on managerial performance; psychological capital and organizational commitment strengthening effect budgetary participation on managerial performance; psychological capital and organizational commitment strengthening effect managerial competence on managerial performance. Keywords: managerial performance, budgetary participation, managerial competence, psychological capital, organizational commitment.